The Role of Corporate Digital Marketing in Customer Loyalty a Survey Study on Customers of the Iraqi Cellular Communications Sector - ALWIDAWI, MHMOOD KADHIM ABED; Khemakhem , Romdhane (Journal of Ecohumanism, 2024)
The research aimed to identify the impact of digital marketing on customer loyalty in the Iraqi cellular communications sector, by knowing the impact of digital marketing in terms of attraction, participation and communication on customer loyalty in the Iraqi cellular communications sector. The researcher relied on the descriptive approach in the research to describe the topic to be studied through a correct scientific methodology, and the quantitative approach for accurate and unbiased measurement and analysis of numerical data collected through questionnaires or surveys, and statistical and mathematical analysis of data or through the SPSS program. The sample size was 371 respondents, and the sample was subjected to the stability test / Cronbach’s Alpha Coefficient. The study concluded that there is a statistically significant correlation and impact of the role of digital marketing in terms of (attraction, participation, communication) in achieving customer loyalty in the Iraqi cellular communications sector. The study recommended the need to focus on the dimensions within digital marketing that are related to and have an impact on customer loyalty, with the need to focus on the importance of customer satisfaction in enhancing customer loyalty in the subject of digital marketing, with the need to conduct a market study and analyze data to know market trends before carrying out the digital marketing process, so that services are provided that satisfy customers in the first place, and then achieve customer loyalty towards them.